Premenstrual syndrome among female medical students of Univerisiti Malaysia Sabah - Ohnmar Thwin; Daw Khin; Daw Khin Saw Naing; Bin Abdullah (American Association for Science and Technology, 2015)
The premenstrual syndrome (PMS) is particularly common in the younger age groups, posing a significant public health problem among young girls. It was noted that, among the female students, PMS was a frequent reason for seeking care at the in-house health clinics of Universiti Malaysia Sabah (UMS). The Faculty of Medicine and Health Sciences (FPSK) took an initiative to explore this problem as the health and quality of life of students are the major concerns of UMS. A cross-sectional study was conducted with 211 female medical students of FPSK to determine the prevalence of premenstrual syndrome (PMS) and to investigate its associated factors. American College of Obstetrics and Gynaecology (ACOG) PMS-criteria-based questionnaires were used. The mean age of students under study was 20.94±0.92 and 51.65% responded to have experienced PMS. Among the somatic symptoms, 70.6% of the studied females complained of breast tenderness, 62. 4% of abdominal bloating, 39.4% of headache and 2.8% of swelling of extremities. Common behavioural symptoms were irritability (80.7%), angry outbursts (66.1%), depression (57.8%), anxiety (53.2%), social withdrawal (31.2%), and confusion (24.8%). Among the reported symptoms; headache, confusion, irritability, social withdrawal, anxiety and swelling of extremities were significantly associated with PMS. However, the relationships between PMS and disturbances in students’ daily physical and mental activities were not statistically significant. As the prevalence estimated by this study was quite high, in-depth studies on PMS of female UMS students need to be conducted.